The Impact of Inclusive Leadership on Employees’ Innovative Behaviors: The Mediation of Psychological Capital - Fang, Yang-Chun; Chen, Jia-Yan; Wang, Mei-Jie; Chen, Chao-Ying (Frontiers in Psychology, 2019)
Employee innovation is the cornerstone of the organization, and the motivation for employee innovative behavior largely depends on the leadership style of the leader. With the economic development of society, the traditional authoritative style of leadership can no longer adapt to the psychological characteristics of employees, who use new-era work concepts, techniques, and social rules (hereafter, new generation workers). Inclusive leadership is based on the concept of “fully inclusive and equitable” in traditional Chinese culture, and it can adapt to the independent needs of new generation employees. At present, the research on the relationship between the traditional leadership style and employee innovative behavior is relatively extensive, but there is little research on the relationship between inclusive leadership style and employee innovative behavior, and this needs further exploration. This paper takes new generation employees as the sample and uses psychological capital as an intermediary variable to explore the influence of inclusive leadership style on the innovative behaviors of new generation employees. We found that inclusive leadership is significantly and positively related to new generation employees’ innovative behaviors. Theoretical and practical implications are discussed.